Relationship between total homocysteine, total cholesterol and creatinine levels in overt hypothyroid patients - Bamashmoos, Saleh A (Springer International Publishing, 2013)
Hypothyroidism is associated with an increased risk for cardiovascular disease, which can not be fully explained by the atherogenic lipid profile, particularly total cholesterol and LDL-C, and other pathogenic factors may be involved. Plasma total homocysteine (tHcy) is an independent risk factor for cardiovascular disease and accelerated atherosclerosis. The aim of this study was to investigate the serum total homocysteine (tHcy) levels and its relation to total cholesterol, creatinine and thyroid hormones fT3, fT4 and TSH levels in overt hypothyroid patients compared to control subjects. In this study thirty recently diagnosed, non-treated overt hypothyroid patients (f=27, m=3) and twenty normal volunteers control (f=18, m=2) were included and subjected to determination of serum tHcy by enzyme immunoassay (EIA) technique, fT3, fT4 and TSH by Elecsys cobas e 601 analyzer, total cholesterol by enzymatic method and creatinine by kinetic method. The data was statistically analysed by SPSS-10 and p values less than 0.05 were considered significant.Our results showed that there were a significant increase of tHcy, TSH, T.cholesterol and creatinine levels by 113%, 12-folds, 58% and 54%, respectively, and a significant decrease of fT4 and fT3 levels by 49.6% and 56.4% , respectively, in hypothyroid patients than in control group. For tHcy (Mean±SD, 24.45±5.50 μmol/l vs 11.48±3.03 μmol/l, respectively; P < 0.001). tHcy was significantly positively correlated with TSH, creatinine and age and negatively correlated with free thyroxine (fT4) and no significant correlations with fT3 and T.cholesterol. In conclusion, our study confirmed the observation of elevated serum tHcy, T.cholesterol and creatinine in overt hypothyroidism and the presence of an inverse relation between tHcy with fT4 and a positive relation with TSH.